Die Imperiale Politik des Vologaises III. und das Bellum Parthicum des Lucius Verus - Hartmann, Udo (Anabasis. Studia Classica et Orientalia, 2019)
This article examines the beginning of the Parthian war of Lucius Verus as well as the aims and political strategies of the Parthian king Vologaeses III. It tries to show that although the Romans regarded Vologaeses’ political actions, especially his occupation of Armenia in 160, as aggressive acts, these actions were not directed against Rome. They can only be explained by the internal political situation in Parthia since 147/148: During the first years of his reign the king who came to power as a usurper tried to enforce control over the important regions of his empire and to eliminate disloyal vassals. Therefore, he appointed new and loyal vassal kings in Mesene in 150/151, in Armenia in 160 and in Osrhoene in 162. However, Rome could not accept his occupation of Armenia. After the failure of the campaigns of Severianus in Armenia in 161 and Cornelianus in Osrhoene in 162 which were intended to reinstall pro-Roman client-kings in these regions, Marcus Aurelius had to send his adoptive brother Lucius Verus against the Parthians in order to restore Rome’s authority in the East. It was therefore the mutual misunderstanding of imperial claims and strategic objectives that triggered the spiral of violence.